Prevalence, Risk Factors, and Impact of Bullying in Boarding School Environments: A Systematic Review - Erindia, Firnanda; Firmansyah, Yura Witsqa; Orizani, Chindy Maria; Jannah, Fitriatul; Istiana, Dina; Suraya, Andi Safutra; Revani, Hilda Dea (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Bullying in boarding schools is a serious issue affecting students’ mental health, social relationships, and academic performance. Boarding schools, especially pesantren in Indonesia, present unique social and institutional contexts that may facilitate bullying. This study conducted a systematic review following PRISMA guidelines. Literature searches were performed in Scopus, ScienceDirect, PubMed, ProQuest, Web of Science, and Google Scholar for studies published between 2020 and 2025. Eligible articles focused on bullying in boarding schools and reported data on prevalence, risk factors, or impacts. Data were synthesized narratively. Bullying is common in boarding schools, including physical, verbal, and relational forms. Key risk factors include low self-esteem, limited resilience, negative parenting styles, unsafe school environments, and peer hierarchies. Bullying was associated with psychological distress, anxiety, depression, peer conflicts, reduced school engagement, and lower academic performance. Prevalence and severity varied across cultural and institutional contexts. Bullying in boarding schools is multifactorial, involving individual, familial, and school-level contributors. Unsafe climates and poor supervision intensify risks, while negative consequences extend beyond immediate harm to long-term mental health, social adjustment, and academic outcomes.